2021
DOI: 10.1111/bjd.19716
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of recalcitrant hidradenitis suppurativa with risankizumab after failure of anti‐tumour necrosis factor alpha

Abstract: DEAR EDITOR, Hidradenitis suppurativa (HS) is a relapsing inflammatory skin disease. The cytokines interleukin (IL)-1b, IL-12, IL-23, IL-17 and tumour necrosis factor (TNF)-a are involved in the inflammatory process. 1 The only approved drug for the treatment of moderate-to-severe cases is adalimumab (a TNF-a inhibitor). However, long-term clinical responses range only from 52 to 57%. 2 Tildrakizumab (anti-IL-23), 3 guselkumab (anti-IL-23) 4 and ustekinumab (anti-IL-12/23) 5 have been successfully used in HS.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…In our experience, and in according to the results reported by Marques et al, 8 risankizumab may reach a rapid decline in disease severity and a substantial improvement of treated subjects' life quality. Also in the mentioned above study, none of the patients included reported any adverse effects.…”
supporting
confidence: 79%
“…In our experience, and in according to the results reported by Marques et al, 8 risankizumab may reach a rapid decline in disease severity and a substantial improvement of treated subjects' life quality. Also in the mentioned above study, none of the patients included reported any adverse effects.…”
supporting
confidence: 79%
“…Three publications report clinical response to risankizumab in four patients treated at psoriasis doses (150 mg sc at week 0, week 4, and every 12 weeks thereafter). [184][185][186] A phase II, double-blind RCT to evaluate the safety and efficacy of two dose levels of risankizumab in adult patients with moderate-to-severe HS is being conducted (NCT03926169). 187 Tildrakizumab is a humanized monoclonal antibody that targets the p19 subunit of IL-23.…”
Section: Surgerymentioning
confidence: 99%
“…So far, only retrospective data on the efficacy of risankizumab within small groups of patients with HS have been reported with acceptable results 58 .…”
Section: +Risankizumab (Abbvie)mentioning
confidence: 99%